2017
DOI: 10.18203/2394-6040.ijcmph20175305
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with exclusive breastfeeding in Kenya: a systematic review

Abstract: World Health Organization (WHO) recommends that infants should be exclusively breastfed (EBF) for the first six months of life. Breast milk is considered an ideal food for the healthy growth and development of the infant. Exclusive breastfeeding is also important in ensuring the health of the mother. Lack of exclusive breastfeeding in the first six months of a child’s life is considered a risk for infant and childhood morbidity and mortality. In Kenya, sub-optimal breastfeeding practices are still prevalent wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 14 publications
3
29
0
Order By: Relevance
“…However the findings are in agreement with those of a Ugandan cross-sectional study that found no association between maternal occupation and exclusive breastfeeding among infants below six months of age [24] and that of an Ethiopian study that found a positive association between maternal unemployment and exclusive breastfeeding [21]. However this finding differed from those of a Kenyan systematic review that found a positive association between maternal occupation and exclusive breastfeeding of infants below six months of age [20]. These disparities in the relationship between maternal occupation and exclusive breastfeeding might need further investigation to ascertain whether maternal occupation has an independent effect on exclusive breastfeeding practice as opposed to its being a proxy measure of socio-economic status or some effect medication might by the different environments in which Ugandan infantmother dyads.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However the findings are in agreement with those of a Ugandan cross-sectional study that found no association between maternal occupation and exclusive breastfeeding among infants below six months of age [24] and that of an Ethiopian study that found a positive association between maternal unemployment and exclusive breastfeeding [21]. However this finding differed from those of a Kenyan systematic review that found a positive association between maternal occupation and exclusive breastfeeding of infants below six months of age [20]. These disparities in the relationship between maternal occupation and exclusive breastfeeding might need further investigation to ascertain whether maternal occupation has an independent effect on exclusive breastfeeding practice as opposed to its being a proxy measure of socio-economic status or some effect medication might by the different environments in which Ugandan infantmother dyads.…”
Section: Discussionsupporting
confidence: 81%
“…Socioeconomic inequalities in exclusive breastfeeding of infants have been reported in both developing and developed countries, however the direction and the magnitude of the association between socio-economic status and exclusive breastfeeding of infants differs between developed and developing countries [19]. In sub-Saharan Africa, a systematic review of Kenyan studies showed that employed mothers were less likely to exclusively breastfeed their infants compared to non-working mothers, and household food insecurity was associated with less likelihood of exclusive breastfeeding practices among women [20]. On the same note, a population based cross-sectional study in Ethiopia, found that unemployed mothers were 9 times more likely to exclusively breastfeed compared to employed mothers [21].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a study in Western Nepal using the Demographic and Health Survey with mother-in-pairs (n=735), reported 42.2% had EIBF. In contrast, a study in Kasarani, Kenya [10] showed that 64.3% of mothers (n=220) were able to do EIBF after birth. Reasons for delayed BF in Nepal included low-birth weight (LBW) infants, CS deliveries, births attended by traditional birth attendants, and ethnically disadvantaged families.…”
Section: Discussionmentioning
confidence: 82%
“…The mothers were recruited into the study every three days during the seven weeks of data collection. [10] Measures The questionnaire was adapted from published literature on the topic, including a study conducted in Kenya by Mututho et al [10] The validated questionnaire used closed-ended questions and was composed of four sections, including demographic characteristics and the participant's perception of early initiation of breastfeeding. Section 1: The sociodemographic characteristics included age, level of education, residence, religion, employment, gravidity, mode of delivery, and location of ANC visit (8 items).…”
Section: Participants' Recruitmentmentioning
confidence: 99%
“…The findings of this study show the practices of mothers about exclusive breastfeeding. Accordingly, the studies conducted in East Africa reported factors affecting actualization of the WHO breastfeeding recommendations "poverty, livelihood and living conditions; early and single motherhood; poor social and professional support; commercial sex work, poor knowledge, myths and misconceptions; HIV and unintended pregnancies, the perception that mothers' breast milk is insufficient for child's growth, child being thirsty and the need to introduce herbal medicine for cultural reasons" [16,18,50,51].…”
Section: Practicesmentioning
confidence: 99%